Effective Policies for Single-Parent Families and Prospects for Policy Reforms in the United States: Concluding Reflections. (July 2022) - Gornick, Janet C.; Maldonado, Laurie C.; Sheely, Amanda
This conclusion engages two questions catalyzed by the articles in this volume. First, which policies are effective in reducing economic hardship among single-parent families overall and minimizing disparities across subgroups? Second, what are the prospects for related reforms in the United States? We draw four lessons from the articles in this volume and from prior research about effective policy design: (1) work-family reconciliation policies are crucial; (2) strengthening and stabilizing employment is necessary, but not sufficient; (3) it is important to support the accumulation of wealth in addition to shoring up income; and (4) policies can be designed to include and protect those single parents and their children who are especially at risk. Turning to the feasibility of policy change in the United States, we conclude that some factors—especially policy elements that encourage self-reliance, shifting public opinion, the COVID-19 crisis, and federalism itself—may enhance opportunities for policy development in support of single parents.